Case report: Removal of a subcutaneous implantable cardiac defibrillator in a pediatric patient with hypertrophic cardiomyopathy after a septal myectomy. Insights on current indications of type of ICD in children with hypertrophic cardiomyopathy and left ventricular tract obstruction - Dolader, Paola; Alegria, Iosune; Martínez Olorón, Patricia; Fernandez-Doblas, Joaquin; Gran, Ferran; Roses-Noguer, Ferran (Frontiers in Pediatrics, 2022)
Hypertrophic cardiomyopathy is a heart muscle disease with an annual incidence between 0.24-0.47/100000 in childhood. Sudden cardiac death is the most common cause of death in this population. Although some medical treatment can decrease the risk of sudden cardiac death, implantable cardioverter defibrillator continues to be the most reliable treatment. Different types of devices and programming strategies can be used in patients with hypertrophic cardiomyopathy depending on each centre and specific patient condition. We report a paediatric patient affected with hypertrophic cardiomyopathy who had and ICD implantation in primary prevention. 4 years later he developed symptomatic left ventricular outflow tract obstruction and a surgical septal myectomy was performed. After the myectomy the patient developed complete left bundle branch block on his 12 lead ECG, and unfortunately none of the S-ICD vectors were suitable after the myectomy and it had to be explanted and replaced for a new transvenous ICD.